Options for Reforming Early Retirement System for Special and Hazardous Occupations in Montenegro - World Bank Group (World Bank, Washington, DC, 2017)
The report is structured as follows. In the first section, authors refer to the demographic and labor market context in Montenegro, which indicate the risks and challenges ahead of the pension system in Montenegro. We also discuss some of the myths that are related to the perception of older workers on the labor market. In the second section, we present the current situation of the pension system in Montenegro in general terms. The third section focuses on the analysis of the available information on the current and future prospects of the early retirement scheme. In section four we present recent developments in the EU and OECD countries related to early retirement solutions, including the developments on early retirement for hazardous and arduous conditions. Special attention is put on the description of the 2008 reform of early retirement of hazardous and arduous conditions in Poland and its outcomes. The polish approach could be used as a model solution in the approach to limit the list of extended service occupations. In section five authors present recommendations for the reform of policies related to the extended service period pensions as well as general early retirement policy in Montenegro.